ANALISIS PUTUSAN KPPU NOMOR 07/KPPU-I/2013 TENTANG DUGAAN PERSEKONGKOLAN PT. ANGKASA PURA II DAN PT. TELEKOMUNIKASI INDONESIA DALAM PENGADAAN LAYANAN E-POS DI BANDARA SOEKARNO-HATTA - Anissa Sesio Julia Putri (Jurnal HUKUM BISNIS, 2018)
Angkasa Pura II and PT. Telecommunications Indonesia, Tbk were suspected of doing violation of competition at Soekarno-Hatta Airport regarding the use of e-Post. PT. Telkom Tbk became the partner of Angkasa Pura II in running the system. According Angkasa Pura II as manager of Soekarno-Hatta, this business was performed to run the synergy between SOEs as instructed by the Minister of SOEs in which in its operation, Angkasa Pura II required Internet services for its tenants. Telkom proposed telecommunication services required by Angkasa Pura II in the form of e-Post. E-Post is a system to check the income of tenants (tenants) running their business in Soekarno-Hatta Airport. Angkasa Pura II was entitled to a percentage of tenants’ profit. This system was intended to ensure total royalties to be received by Angkasa Pura. Business Competition Supervisory Commission (KPPU), in the judge’s consideration outlined their decision in decision No. 07/KPPU -I/2013. Both companies are considered legally and convincingly violating Article 15 paragraph (2) of Law No. 5 of 1999 on Prohibition of Monopolistic Practices and Unfair Competition. Angkasa Pura II and Telkom declared that e-Post cooperation isin accordance with the rules and regulations prevailing in Indonesia. Having outlined the chronology of cases associated with the relevant regulations, it can be seen that Angkasa Pura II did not perform bid rigging or perform certain agreements with Telkom Indonesia, because it is part of SOEs synergy.Keywords: Conspiration, SOE, e-Post, Tender.